Pengaruh Kompetensi, Pelatihan Dan Budaya Perusahaan Terhadap Kinerja Karyawan Pada Pt World Innovative Telecomunication Medan (Distributor Tunggal Oppo Smartphone) - Masro Iman Marbun; Hendry Hendry (Journal of Economic, Bussines and Accounting (COSTING), 2022)
The purpose of this study is to determine the effect of Competence on Performance, know the effect of Training on Performance, know the influence of Corporate Culture on Performance and know the influence of Competence, Training, Company Culture simultaneously on employee performance of PT World Innovative Telecomunication Medan . This research was conducted at PT World Innovative Telecomunication Medan. The population is that all employees of PT World Innovative Telecomunication Medan are 183 people. The sampling technique is a saturated sample so that the size of the sample is 127 people. The results of the study were a t valuecalculating Competencies 6,223>1,979, t-valuescalculatingTraining 3,623 > 1,979 t valuescalculating Corporate Culture 2,625 > 1,979, and F valuescalculating Competencies, Training, Corporate Culture simultaneously 91,606 > 2.493 and the sig value < 0.05. The conclusion of the study is Competence has a significant effect on Employee Performance where the sig value < 0.05, Training has a significant effect on Employee Performance where the sig value < 0.05, Company Culture has a significant effect on Employee Performance where the sig value is more < 0.05 and serentak Competence, Training, Corporate Culture have a significant influence on employee performance at PT World Innovative Telecomunication Medan where the sig value < 0.05 Keywords : Competence, Training, Company Culture, Performance.